Dawn of Small Worlds Dwarf Planets, Asteroids, Comets - Moltenbrey, Michael (Astronomers' Universe,, 2016)
This book gives a detailed introduction to the thousands and thousands of smaller bodies in the solar system. Written for interested laymen, amateur astronomers and students it describes the nature and origin of asteroids, dwarf planets and comets, and gives detailed information about their role in the solar system. The author nicely reviews the history of small-world-exploration and describes past, current and future space craft missions studying small worlds, and presents their results. Readers will learn that small solar system worlds have a dramatically different nature and appearance than the planets. Even though research activity on small worlds has increased in the recent past many of their properties are still in the dark and need further research.